Nilai -Nilai Pendidikan Krakter Anak Usia Dini Dalam Al Qur’an Surah Al -Lukman Ayat 13-19 (Analisis Tafsir Al-Misbah Karya M. Quraisy Shihab) - Amin, Abdul; Hudin, Hafid; Kurniawan, Heri; Luqman (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study analyzes the values of early childhood character education in Surah Luqman verses 13-19 based on the tafsir Al-Misbah by M. Quraish Shihab. This surah contains fundamental teachings related to character building, including tawhid, filial piety, honesty, responsibility, patience, tolerance, as well as humility and courtesy. Through the tafsir study method, this study found that Quraysh Shihab emphasizes tawhid-based character education as the main foundation, followed by strengthening morals and ethics in social life. These values are taught through Luqman's advice to his son, which is not only relevant in the Islamic context, but also universal in the formation of early childhood personality. The results show that Surah Luqman verses 13-19 emphasize several fundamental character values, including tawhid, filial piety, honesty, responsibility, patience, tolerance, humility, and courtesy. These values play an important role in shaping children's moral and ethical foundations from an early age. This study highlights the importance of integrating these Qur'anic values in early childhood education to form individuals of strong character and deep spiritual awareness. This research contributes to Islamic education by providing insights into the implementation of character education based on Qur'anic teachings